Potential key factors involved in regulating adipocyte dedifferentiation. Issue 3 (19th November 2021) - Liu, Shiqi; Wang, Liyi; Ling, Defeng; Valencak, Teresa G.; You, Wenjing; Shan, Tizhong
Abstract: Adipocytes are the key constituents of adipose tissue, and their de‐differentiation process has been widely observed in physiological and pathological conditions. For obese people, the promotion of adipocyte de‐differentiation or maintenance of an undifferentiated state of adipocytes may help to improve their metabolic condition. Thus, understanding the regulatory mechanisms of adipocyte de‐differentiation is necessary for treating metabolic diseases. Attractively, in addition to intracellular signals regulating adipocyte de‐differentiation, external factors such as temperature and pressure also affect adipocyte de‐differentiation. In this review, we summarize the recent progress in the field and discuss the regulatory roles and mechanisms of involved endogenous and exogenous factors during the process of de‐differentiation. Abstract : Adipocytes are the key constituents of adipose tissue, and their de‐differentiation process has been widely observed in physiological and pathological conditions. Understanding the regulatory mechanisms of adipocyte de‐differentiation is necessary for treating metabolic diseases. In this review, we summarize the recent progress in the field and discuss the regulatory roles and mechanisms of involved endogenous and exogenous factors during the process of de‐differentiation.